THE BITING ACTIVITY OF ANOPHELES DTHALI IN A RURAL AREA OF MAMASANI UNDER IMPACT OF ORGANO-PHOSPHOROUS SPRAYING, SOUTHERN IRAN - N Eshghy; E Javadian; H Ladony; AV Manouchehri (Tehran University of Medical Sciences, 1983)
Anopheles dthali Patton which is one of the 7 malaria vectors in Iran was not taken in to consideration until November 1965 when definite sporozaites were found for the first time in its salivary glands in Bandar Abbas, south of Iran. Afterwards, efforts have been made to get complete ecological and epidemiological information on this species. The areas of study were two districts of Mamasani, an agricultural area, located 200 km north of the Persian Gulf. The objective of the present paper is to summarize and discuss briefly the field investigations concerning the nocturnal biting cycle and behavior of An. dthali as well as the comparative attractiveness of man and cattle to these vectors under the impact of the organophosphouous insecticides. On the basis of the data collected, it was found that most of the bites take place between 21.00-24.00 hr. Biting pattern under local condition indicated that the number of bites per cow was much greater than the number of bites per man.